Pemanfaatan Makroalga oleh Masyarakat Binuangeun Lebak Banten - Billyardi Ramdhan; Suhendar; Jujun Ratnasari (The Ethnobiological Society of Indonesia, 2021)
Binuangeun Beach, Lebak Regency, Banten Province, is one of the south coasts of Java which is still natural and virgin. This condition holds biological potential, one of which is macroalgae. Coastal community interactions with the potential of algae is part of everyday life. This article aims to reveal the potential of macroalgae found on the coast based on the knowledge of the people. Efforts to collect information/ emic from the community are carried out by collecting specimens using the Quadrant Transect method for sampling macroalgae species, then Plant Interviews are carried out to record community emics about the use of macroalgae found in the field. The Plant Interview was conducted in a structured manner. Interviews were conducted with two key informants from the local community. From the observations obtained 11 species. Among the beneficial species, it is noted that some of the species used are Ulva lactuca which can be used as food/ lalab; Turbinaria ornata is used as a trading / traded commodity, Sargassum sp as a trading/ traded commodity, foodstuff, and medicine; Halimeda tuna is used as paint and chalk and Enteromorpha compress is consumed. From these data it can be concluded that Binuangen Beach Banten has the potential to be developed into a source of additional nutrition, commercial and medicinal properties.